“Sejam todos bem-vindos?”: valores pessoais e orientação para a diversidade em profissionais do turismo - Magalhães, Antônio Wagner Chagas (2019)
Tourism, in addition to economic and market aspects, reflects on social and cultural aspects, as it involves the contact and interaction between the traveler and the community visited. Due to the proximity to people of different origins, races and cultures, it is required an understanding of the personal values and orientation towards the diverse one by the professionals who work in companies and sectors associated to the tourist activity, known as tourist trade. In this context, this research aims to investigate the relationship between the dimensions of personal values, conceived as criteria that directly interfere with attitudes, preferences and even in human behavior (SCHWARTZ, 2005a; 2012), as opposed to orientation to the diverse, represented by the UDO-Universal Diverse Orientation construct, which reflects an attitude of awareness and acceptance of similarities and differences between people (MIVILLE et al., 1999). In order to achieve the research objective, a quantitative study was carried out using a questionnaire composed of two scales, the Portrait Values Questionnaire (PVQ) and the Miville-Guzman Diversity Scale (M-GUDS-S), both validated in Brazil. The sample, made up of 356 people, is composed of a very heterogeneous group of professionals from the tourist trade, who expressed, in their answers, a favorable orientation to diversity in the three dimensions of the UDO and with respect to personal values presented greater similarity to the values of the dimensions self-transcendence and openness to change. When related, the dimensions of the UDO with the dimensions of personal values, the results show that no positive relations were identified in the diversity of contact with any dimension of personal values, in the relativistic appreciation the only significant and positive correlation was in the dimension self-promotion and, for Finally, comfort with differences correlated significantly and positively only with the values of the self-transcendence dimension. In general, the study of personal values and orientation to the diverse allows several possibilities of additional investigation, which allows recommendations for future research. Finally, it is hoped that the research will contribute to the improvement of the public and private management of the sectors involved with the tourist activity, and, as such, may help to guide diversity training and policies.